Influence of complex defects on electrophysical properties of GaP light emitting diodes - Konoreva, O.; Malyj, E.; Mamykin, S.; Petrenko, I.; Pinkovska, M.; Tartachnyk, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
In order to estimate the role of complex defects on GaP light emitting diodes (LED) operation, luminescent and electrical characteristics of GaP LEDs irradiated with reactor neutrons have been studied. It has been stated that nonradiative levels of radiation defects affect electroluminescence quenching. From the analysis of the tunnel current, the density of dislocations in the depleted part of the p–n junction was obtained. Neutron induced disorder regions do not change the tunnel component of the direct current of red diodes, increasing the dislocation density, because the carrier flow along the “tunnel shunts” is blocked.